Vibration Attenuation of FG–GR-Laminated Composite Cantilever Rectangular Plate Integrated with Piezoelectric Actuator and Sensor - Jiang, Y.; Zhang, Y. F.; Zhang, W.; Guo, X. T. (Journal of Vibration Engineering & Technologies, 2024)
Purpose Due to the remarkable physical properties of the graphene, the graphene-reinforced composite structures can be applied generally in the aerospace and other engineering fields. However, for the vibration amplitude attenuation of the graphene-reinforced structures, this is a challenging problem for researchers. The integrated piezoelectric sensors and actuators have many advantages as active intelligent materials in many mechatronic and vibration control systems. Therefore, the integrated piezoelectric actuator and sensor are designed by sticking piezoelectric patches on the surface of the FG–GRLCC rectangular plate to study the vibration amplitude attenuation. Methods Based on the extended Halpin–Tsai micromechanical model, the elastic coefficients of the graphene-reinforced plate are formulated. Considering the classical laminated plate theory, the Hamilton principle, and the piezoelectric coupling effect, the dynamic equations of the piezoelectric FG–GRLCC rectangular plate are derived. The ordinary differential control equations of motion for the plate are obtained by applying the Galerkin method. To reduce vibration amplitude, the parameters of the positive position feedback (PPF) controller are designed using the Routh–Hurwitz stability criterion and the H ∞ optimal strategy. Results The vibration characteristics for the piezoelectric FG–GRLCC rectangular plate with four different graphene distributions are studied. Numerical simulations are given to study the vibration amplitude attenuation via the proposed PPF control algorithm. In addition, the PPF control algorithm and the velocity feedback controller are compared. Conclusion The designed PPF control algorithm can reduce the vibration amplitude for the four different graphene distribution for the FG–GRLCC rectangular plate subjected to the transverse excitation. In addition, the key of the vibration suppression is that the frequency of the PPF controller is same with the frequency of the structure.